(untitled) (Kinesiology, 2018)
The purpose of this investigation was to determine the acute effects of back squats on countermovement jump performance across multiple sets using a strength-power potentiation complex training protocol. Fifteen elite volleyball players performed three unloaded countermovement jumps (CMJ) following three repetitions of the back squat performed at either 65% or 87% of 1-RM, respectively, repeated for 10 sets. A control session of three CMJs was also repeated for 10 sets. Mean jump height performance was enhanced compared to performing CMJs only irrespective of which intensity was used (65% 1-RM: +3.3 ± 2.2% [CI: 1.0 to 5.6]; 87% 1-RM: 2.6 ± 1.9% [CI: 0.7 to 4.5]). Subjects with a greater relative strength possessed a very likely large (97%; ES = 1.51) chance of improvement in jump height across 10 sets of the protocol prescribed using the intensity of 87% 1-RM and a likely moderate (89%; ES = 0.94) and very likely large (97%; ES = 1.76) chance of improvement in maximum concentric impulse (N·s) using intensities of 65% and 87%1-RM, respectively. Performance (jump height and maximum concentric impulse) may be enhanced across 10 sets of the strength power potentiation complex training protocol prescribed irrespective of intensity, with a greater effect observed for the subjects with a greater relative strength and with the 87% 1-RM heavy load back squat condition. In practice, coaches should consider the athlete’s strength level when designing such a complex training protocol to generate any post-activation potentiation effect across multiple alternating sets to enhance jump performance. Key words: complex training, postactivation potentiation, PAP, conditioning stimulus